Adrenalectomies in children and adolescents in Germany – a diagnose related groups based analysis from 2009-2017 - Konstantin L. Uttinger; Konstantin L. Uttinger; Maria Riedmeier; Joachim Reibetanz; Thomas Meyer; Christoph Thomas Germer; Christoph Thomas Germer; Martin Fassnacht; Armin Wiegering; Armin Wiegering; Armin Wiegering; Verena Wiegering (Frontiers in Endocrinology, 2022)
BackgroundAdrenalectomies are rare procedures especially in childhood. So far, no large cohort study on this topic has been published with data on to age distribution, operative procedures, hospital volume and operative outcome.MethodsThis is a retrospective analysis of anonymized nationwide hospital billing data (DRG data, 2009-2017). All adrenal surgeries (defined by OPS codes) of patients between the age 0 and 21 years in Germany were included.ResultsA total of 523 patient records were identified. The mean age was 8.6 ± 7.7 years and 262 patients were female (50.1%). The majority of patients were between 0 and 5 years old (52% overall), while 11.1% were between 6 and 11 and 38.8% older than 12 years. The most common diagnoses were malignant neoplasms of the adrenal gland (56%, mostly neuroblastoma) with the majority being younger than 5 years. Benign neoplasms in the adrenal gland (D350) account for 29% of all cases with the majority of affected patients being 12 years or older. 15% were not defined regarding tumor behavior. Overall complication rate was 27% with a clear higher complication rate in resection for malignant neoplasia of the adrenal gland. Bleeding occurrence and transfusions are the main complications, followed by the necessary of relaparotomy. There was an uneven patient distribution between hospital tertiles (low volume, medium and high volume tertile). While 164 patients received surgery in 85 different “low volume” hospitals (0.2 cases per hospital per year), 205 patients received surgery in 8 different “high volume” hospitals (2.8 cases per hospital per year; p<0.001). Patients in high volume centers were significant younger, had more extended resections and more often malignant neoplasia. In multivariable analysis younger age, extended resections and open procedures were independent predictors for occurrence of postoperative complications.ConclusionOverall complication rate of adrenalectomies in the pediatric population in Germany is low, demonstrating good therapeutic quality. Our analysis revealed a very uneven distribution of patient volume among hospitals.